EFFECT OF FINANCIAL LITERACY ON INVESTMENT DECISION (STUDY CASE ON STUDENTS OF FACULTY OF ECONOMY AND BUSINESS AT SAM RATULANGI UNIVERSITY) - Viantara, Afriandy; Worang, Frederik G.; Tumewu, Ferdinand J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: Financial literacy is the ability to manage funds owned in order to develop and live more prosperously in the future. The bad impact of a poor level of financial literacy is that it can trigger a variety of financial problems. One of the most common financial problems is the issue of financial planning for the future (investment). The first issue regarding investment is the tendency of people with low literacy levels to make mistakes in allocating money they have. The purpose of this research to analyze the effect of financial literacy on investment decision on economy and business students at sam ratulangi university that has been measured through general personal finance knowledge, saving and borrowing, insurance, and investment and to identify dimension of financial literacy that the most effect on investment decision among students.This research uses causal type with a quantitative approach. The population of this study is the students who ever make an investment. sample of this research is 100 respondents with data obtained through questionnaires.The finding of this research shows that general persona finance knowledge, saving and borrowing, insurance and investment are significantly affect investment decision among students simultaneously. Partially, only investment variable that affect investment decision among students. As the recommendation, Financial literacy is a very important thing to support investment activities so students need to increase these factors.Keywords: financial literacy, investment decision